Utilization of a Continuous Pericapsular Nerve Group (PENG) Block with an Opioid-Sparing Repair of a Femoral Neck Fracture in a Pediatric Patient - Karla Wyatt; Moustafa Zidane; Chyong-jy Joyce Liu (Case Reports in Orthopedics)
In the pediatric population, femoral neck fractures are usually associated with high-impact trauma and often present with pain in the groin area. Regional anesthesia can offer adjunctive therapy for acute pain management. Various techniques have been employed to circumvent pain related to hip fractures and resultant hip surgery. Neuraxial, lumbar plexus, caudal, epidural, fascia iliaca, and femoral continuous nerve block techniques are advantageous in mitigating hip pain. However, these approaches require patient repositioning during placement and carry the potential for motor blockade with resultant weakness. A newly described method, the Pericapsular Nerve Group (PENG) block, allows for analgesia of the anterior hip capsule via the obturator, accessory obturator, and femoral nerves while sparing motor blockade. PENG blockade has demonstrated efficacy in both adult and pediatric patients. Herein, we describe the perioperative course of a 9-year-old girl with a transcervical femoral neck fracture who underwent an opioid-sparing open repair with the utilization of a continuous PENG block. PENG blockade via a continuous nerve block resulted in optimal analgesia and markedly reduced perioperative opioid consumption with preserved motor function. Our experience facilitated early discharge and rehabilitation mobility while reducing potential rebound hyperalgesia and enabling parental/patient satisfaction.